FAKTOR-FAKTOR YANG BERPENGARUH TERHADAP PERUBAHAN LABA - Chermian Eforis; Setyani Metta Lijaya (Ultimaccounting Jurnal Ilmu Akuntansi, 2021)
Abstract— Profit is one of company’s performance indicator and it will give good signal to investor when it increases. Based on previous studies, there are some financial ratios that have effects toward change in profit such as current ratio, return on asset (ROA), total asset turnover (TATO), and debt to asset ratio (DTA). This research aims to find the effect of current ratio, ROA, TATO and DTA towards change in profit. Manufacturing companies in the consumer goods industry which is listed on the Indonesia Stock Exchange (BEI) from 2016-2019 is the object of this research and purposive sampling as a sampling method. There are several criterias for sample selection such as published an audited financial statement for 4 years consecutive in 2016-2019; using Rupiah as a currency report in Financial statement; and has profit for 4 years consecutive in 2016-2019. There are 27 companies that meet all the criterias. The result of this research were (1) current ratio and debt to total asset had no significant effect towards changes in profit, (2) return on asset had a positive significant effect towards changes in profit, (3) total asset turnover had a negative significant effect towards changes in profit. Current ratio has no significant effect due to gain of intangible assets, gain of unrealized foreign exchange and financial income. The reason for debt to total asset is because the increase of liability is in line with the increase of asset, especially fixed assets. When fixed assets expand, total sales have increase along with profit change Keywords: Changes in Profit; Current Ratio; Debt to Asset Ratio; Return on Asset; Total Asset Turnover